2004
DOI: 10.3168/jds.s0022-0302(04)73447-5
|View full text |Cite
|
Sign up to set email alerts
|

Invited Review: Selection on Net Merit to Improve Lifetime Profit

Abstract: Genetic selection has made dairy cows more profit-able producers of milk. Genetic evaluations began with 2 traits measured on a few cows but now include many traits measured on millions of cows. Selection indexes from USDA included yield traits beginning in 1971, productive life and somatic cell score beginning in 1994, conformation traits in 2000, and cow fertility and calving ease in 2003. This latest revision of net merit should result in 2% more progress, worth 5 million dollars/yr nationally, with improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
119
1
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(134 citation statements)
references
References 18 publications
9
119
1
5
Order By: Relevance
“…For example, VanRaden (2004) showed that the size of USA cattle increased by 0.8 genetic standard deviations between 1990 and 2000 and predicted that selecting for reduced size in the USA index Net Merit, would reverse the genetic trend in size (−0.6 genetic standard deviations over the next decade). The genetic trend in protein yield would remain similar over the two decades (33 and 35 kg for actual 1990 to 2000 and expected genetic trend, respectively).…”
Section: Selection For Gross Feed Efficiencymentioning
confidence: 99%
“…For example, VanRaden (2004) showed that the size of USA cattle increased by 0.8 genetic standard deviations between 1990 and 2000 and predicted that selecting for reduced size in the USA index Net Merit, would reverse the genetic trend in size (−0.6 genetic standard deviations over the next decade). The genetic trend in protein yield would remain similar over the two decades (33 and 35 kg for actual 1990 to 2000 and expected genetic trend, respectively).…”
Section: Selection For Gross Feed Efficiencymentioning
confidence: 99%
“…Veerkamp (1998) suggested that feed intake and BW, or indirect indicators of these traits such as conformation traits, could be used in a selection index to increase economic efficiency of milk production. Likewise, other selection indices to improve economic efficiency of milk production are described and reviewed by VanRaden (2004) and Shook (2006), and therefore, will not be discussed here. The greatest challenges in using such indices are in determining which traits to include in the index and how to weight them in order to maximise economic gain and prevent 'double counting' of feed costs associated with each trait included in the index (Veerkamp, 1998).…”
Section: Estimates Of Feed Efficiency In Dairy Cattlementioning
confidence: 99%
“…Because of the economic importance of fertility, reproduction traits have been incorporated as a selection criterion for dairy cattle in many countries (e.g., VanRaden, 2004). Knowledge of those relationships in dairy goats is limited.…”
mentioning
confidence: 99%